Alternative splicing regulates autophagy in response to environmental stresses in cucumber (Cucumis sativus). Issue 1 (31st December 2023) - Thanapipatpong, Pawaree; Vuttipongchaikij, Supachai; Chomtong, Thitikorn; Puangtame, Wilasinee; Napaumpaipond, Pondpan; Gomez, Leonardo D.; Suttangkakul, Anongpat
Abstract : Autophagy is important for cell survival during stress and nutrient recycle. However, the mechanisms involved in regulating autophagy in cucumber have not been determined. Here, we analyzed the transcript abundance of key autophagy genes in the conjugation pathway including ATG3, ATG4, ATG5, ATG7, ATG8, ATG10, ATG12 and ATG16 in response to nitrogen deficiency, pathogen infection and oxidative stress in Cucumis sativus . ATG8 protein abundance was analyzed using immunoblot analysis. Seven out of 13 autophagy genes studied have splice variances including ATG3, ATG4, ATG5, ATG8b, ATG8c, ATG8e and ATG10 . All except ATG5 have changes in transcript variances abundance upon nitrogen starvation, indicating regulation via alternative splicing is pervasive in autophagy genes. This is the first report of alternative splicing in autophagy genes in cucumbers. However, transcription control is also important, especially in ATG4, and those without transcript variances. Moreover, different environment cues regulate autophagy genes through different mechanisms. The ATG8 protein tag was also regulated at the protein level through post-translational modification and blockage of degradation. This work shows that the regulation of autophagy in cucumber is complex and involves many mechanisms. Better understanding of autophagy regulation would thus help breeding plants that perform better even under environmental stresses.